THE PLACE OF ARTIFICIAL INTELLIGENCE IN MEDICINE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article presents a comprehensive analysis of the application of artificial intelligence (AI) technologies in healthcare, with particular emphasis on diagnostic accuracy, predictive modelling, and the quality of medical education. The roles of machine learning, deep learning, and natural language processing in clinical decision-making are systematically examined. The findings confirm that AI represents a transformative and multifaceted opportunity in modern medicine.